2011
DOI: 10.1016/j.bbrc.2011.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent SUMOylation of the brain-specific scaffolding protein GISP

Abstract: G-protein coupled receptor interacting scaffold protein (GISP) is a multi-domain, brain-specific protein derived from the A-kinase anchoring protein (AKAP)-9 gene. Using yeast two-hybrid screens to identify GISP interacting proteins we isolated the SUMO conjugating enzyme Ubc9. GISP interacts with Ubc9 in vitro, in heterologous cells and in neurons. SUMOylation is a posttranslational modification in which the small protein SUMO is covalently conjugated to target proteins, modulating their function. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…We, and others have also identified other synaptic SUMO substrates e.g. [12], [13] and SUMOylation has been implicated in several clinically important neurological and neurodegenerative diseases [14]. Interestingly, although there is currently no evidence to suggest that AMPARs are direct targets of SUMOylation [8], we have recently demonstrated that SUMOylation can regulate AMPAR trafficking during homeostatic synaptic plasticity [13].…”
Section: Introductionmentioning
confidence: 79%
“…We, and others have also identified other synaptic SUMO substrates e.g. [12], [13] and SUMOylation has been implicated in several clinically important neurological and neurodegenerative diseases [14]. Interestingly, although there is currently no evidence to suggest that AMPARs are direct targets of SUMOylation [8], we have recently demonstrated that SUMOylation can regulate AMPAR trafficking during homeostatic synaptic plasticity [13].…”
Section: Introductionmentioning
confidence: 79%
“…However, SUMOylation appears to play a much more pervasive regulatory role in cells; recent studies have shown SUMOylation of ion channels, membrane-bound receptors, solute carriers, and mitochondrial or neuronal scaffolding and signaling proteins (4)(5)(6), leading to the notion that SUMOylation is a core regulatory process in all cellular subcompartments. This triggered substantial activities to develop tools for the discovery and validation of SUMOylation substrates in cells, which has proven difficult.…”
mentioning
confidence: 99%
“…For example, SUMOylation can promote non-covalent interactions with proteins containing SUMO interacting motifs (SIMs), occlude binding sites, modulate protein localisation and/or regulate proteostasis [55]. In particular, SUMOylation is a key regulator of neuronal function [56], with numerous neuronal proteins shown to be targets for activity-dependent modification, including several involved in neurotransmission and plasticity such as the kainate-type glutamate receptor subunit GluK2 [57], the transcription factor CREB [58] and the postsynaptic density scaffold GISP [59].…”
Section: Sumoylationmentioning
confidence: 99%